Physicochemical Studies on the Interaction between Sodium Dodecyl Sulfate and Methylene Blue in Methanol-Water Mixed Solvent Media - Pawan Shah; Nilam Jha; Ajaya Bhattarai (Journal of Chemistry)
The surface activity and the process of micellization of sodium dodecyl sulfate (SDS) with methylene blue (MB) in a methanol-water mixed solvent system were investigated by tensiometry and conductometry at 298.15 K. The measurements of surface tension and conductivity of SDS-MB complex were carried up to 0.3 volume fractions of methanol because the resulting complex appeared turbid above 0.3 volume fractions of methanol. The critical micelle concentration (CMC) of the SDS was determined from both tensiometry and conductometry. The CMC of SDS increased with the increasing volume fraction of methanol due to the inclusion of methanol in the micelles and decreased in the presence of methylene blue due to the reduction of electrostatic repulsion within the anionic moiety of SDS by the positive charge of the added dye. Different properties like surface excess concentration Γmax, minimum surface area Amin, Gibbs free energy of micellization ΔGmo, surface pressure (πCMC), efficiency of a surfactant (pC20), packing parameter P, and standard free energy interfacial adsorption ΔGadso of SDS in the absence/presence of MB were calculated. On the basis of ΔGmo values, it was noticed that the increasing volume fraction of methanol disfavors the micellization of SDS, while the presence of MB increased the efficiency of SDS making the micellization process more spontaneous.